Parametric modeling in cold extrusion of Al 2014 alloy using Taguchi method–based GRA - Anupama Francy K.; Venkata Sai Sudheer S.; Naga Krishna N.; Naveen Kumar Ch.; Venu M. (Journal of Engineering and Applied Science, 2025)
Abstract Cold extrusion is a fundamental metal forming technique and involves subjecting a block of material to high pressure as it passes over a die orifice of exact profile. The method remains influenced by numerous parameters including die angle, ram speed, lubricant type, extrusion ratio, die land height, workpiece geometry and material properties. Accurate estimation of extrusion force is critical, as it significantly impacts product quality. The current study explores the effects of die angle (15°, 25° and 35°), ram speed (1.5 mm/min, 3 mm/min and 4.5 mm/min) and lubricant (coconut oil, petroleum jelly and grease) on extrusion force, compressive strength, time and displacement. L27 orthogonal array design is used to conduct the tests, and aluminium 2014 alloys are chosen as the workpiece material. Analysis of variance (ANOVA) is employed to assess the significance of extrusion process parameters. Results depict that die angle has a greater impact on extrusion force compared to ram speed and lubricant. Multi-parameter optimization using Grey relation analysis with equal weighting for extrusion force, compressive strength, time and displacement have been considered. The optimal conditions for minimizing extrusion force, compressive strength and time, while maximizing displacement, are obtained at a die angle of 15°, ram speed of 3 mm/min and lubricant grease.